2003
DOI: 10.1110/ps.0224403
|View full text |Cite
|
Sign up to set email alerts
|

Role of histidine interruption in mitigating the pathological effects of long polyglutamine stretches in SCA1: A molecular approach

Abstract: Polyglutamine expansions, leading to aggregation, have been implicated in various neurodegenerative disorders. The range of repeats observed in normal individuals in most of these diseases is 19-36, whereas mutant proteins carry 40-81 repeats. In one such disorder, spinocerebellar ataxia (SCA1), it has been reported that certain individuals with expanded polyglutamine repeats in the disease range (Q 12 HQHQ 12 HQHQ 14/15 ) but with histidine interruptions were found to be phenotypically normal. To establish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 34 publications
8
38
0
1
Order By: Relevance
“…This result demonstrates the faster aggregation kinetics of Q41 when compared to Q22, in agreement with previous studies performed with synthetic polyQ peptides. 10,18 We also analysed the aggregation kinetics of cleaved Q41 and Q22 using a Coomassie blue staining SDS-PAGE method (Supplementary Data Figure S1c and d). This method confirms that Q41 peptides aggregate much faster than Q22 ones (at similar concentration), and shows in addition that the aggregation kinetic of Q22 depends on its concentration (Q22 (1.2 mM) aggregates faster than Q22 (0.2 mM)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result demonstrates the faster aggregation kinetics of Q41 when compared to Q22, in agreement with previous studies performed with synthetic polyQ peptides. 10,18 We also analysed the aggregation kinetics of cleaved Q41 and Q22 using a Coomassie blue staining SDS-PAGE method (Supplementary Data Figure S1c and d). This method confirms that Q41 peptides aggregate much faster than Q22 ones (at similar concentration), and shows in addition that the aggregation kinetic of Q22 depends on its concentration (Q22 (1.2 mM) aggregates faster than Q22 (0.2 mM)).…”
Section: Resultsmentioning
confidence: 99%
“…8,9,17 Likewise, circular dichroism (CD) experiments performed on synthetic polyQ peptides solubilized by treatment with strong acidic solvent used to destroy aggregates also revealed no structural difference between short and long polyQ. 10,18 To compound the debate, we have designed a simple strategy to produce concentrated polyQ peptides by specific cleavage from a glutathione-Stransferase (GST) carrier. This approach presents unique advantages over other strategies: it allows us to produce soluble polyQ in native-like conditions starting from a pure, well characterized and soluble protein, thus avoiding chemically synthesized peptides which, to be solubilized, need treatment with strong acidic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The (LEHQ 9 ) 9 polypeptide (approximating a random coil of 108 amino acids with a predicted contour length of about 41 nm) was designed on the basis of the known structure of polyglutamine peptides (20,21) and the N-terminal inactivation chain of Drosophila Shaker K ϩ channel (22). The coding regions of mouse TRESK and human 14-3-3 (the latter differs only in two amino acids from the mouse ortholog) were amplified by PCR from our pEXO-mTRESK clone (15) and pcDNA3.1-h14-3-3 (received from Andrey S. Shaw) with the mTRESK-s/mTRESK-a and h14-3-3-s/h14-3-3-a primer pairs, respectively.…”
mentioning
confidence: 99%
“…However, the observed circular dichroism spectra indicated that for both the short and long interrupted peptides, the β -sheets were intra-molecularly hydrogen bonded with the histidine residues found at the head of the hairpin. In contrast, the uninterrupted peptides adopted tightly linked, wide intermolecular β -sheets [48, 49]. Additional alkylation experiments determined that the histidine residues in the interrupted peptide aggregates are solvent-accessible, fitting with the previously proposed structural model [48, 49].…”
Section: Histidine Interruptionsmentioning
confidence: 63%
“…In an in vitro comparison of secondary structure conformation, aggregates of expanded and unexpanded versions of both interrupted and pure polyQ peptides adopted β -sheet conformation [48, 49]. However, the observed circular dichroism spectra indicated that for both the short and long interrupted peptides, the β -sheets were intra-molecularly hydrogen bonded with the histidine residues found at the head of the hairpin.…”
Section: Histidine Interruptionsmentioning
confidence: 99%